Identifying Training Needs and Competency Gaps among Barangay Secretaries in LGU Siquijor: Basis for Capacity-Building - Rosalina E. Catid; Joven M. Jalbuna; Peter L. Boncales; John Anthony Jimenez (Research Synergy Foundation, 2026)
This community needs assessment examined the skills and training needs of barangay secretaries in the Local Government Unit (LGU) of Siquijor in response to the growing issue of skills mismatch in public service delivery. Although previous studies have explored capacity challenges in public administration, localized evidence on the competencies and administrative experiences of barangay-level officials remains limited. Grounded in Max Weber’s social action theory, the study employed a descriptive mixed-methods approach using structured questionnaires and thematic analysis of qualitative responses from 18 purposively selected barangay secretaries. Quantitative findings revealed moderate proficiency in administrative, communication, and management functions, with composite means ranging from 2.68 to 2.85. However, competency gaps were identified in project proposal development, monitoring and evaluation, and needs assessment, each obtaining a mean score of 2.39. Qualitative findings supported these results and identified challenges related to heavy workloads, limited digital literacy, inadequate legal knowledge, and resource constraints. Respondents also expressed high demand for training in digital archiving, program planning, participatory governance, ethical leadership, and advanced communication, with an overall composite mean of 3.69. The findings indicate that proficiency in routine tasks does not fully align with the competencies required for complex governance functions. The study provides an empirical basis for developing targeted and context-responsive capacity-building interventions for local government officials.